The Role and Importance of Comprehensive Management Systems in Enterprises Concerned with Hard Coal Exploitation - Jarosław BRODNY (Communications of International Proceedings, 2021)
Due to high competition on the energy raw material market as well as information and communication technology (ICT) changes in the global economy, comprehensive production management systems are increasingly being used in production processes. Factors that are said to be responsible for the growing importance of these systems, in addition to competition, involve the need to adapt to market requirements, integration and improvement of the management process and information flow as well as implementation of new technologies and innovative solutions. The issues of quality and environmental impact are also crucial. In the case of companies involved in mining production, safety issues are also of great importance. Therefore, the main purpose of using these systems in mining is to improve the efficiency and safety of processes. In the case of mining operations, various systems are used, which integrate sub-areas of these processes and enable efficient management of human and material resources. Currently, these systems are based on very advanced IT solutions and are characterized by an increasingly user-friendly interface. The article focuses on the currently commonly used system to support the management process in mining companies. Its basic functions along with their importance for the process of mining exploitation were discussed. The possibility of using the system to analyze the effectiveness of mining machinery and other equipment was also presented. The use of IT solutions and industrial automation systems, as support systems, creates opportunities for improving the efficiency of exploitation and mining production. The presented example is a confirmation of this thesis simultaneously indicating the directions of development of IT management systems in mining companies.
Keywords: Mining Production; Hard Coal; Management; Information Systems; Mining Operations; Industrial Automation Systems